Nutritional evaluation of leaf meal added crop residue based feed block for growing male buffaloes - DWIVEDI, P N; PATHAK, P K (The Indian Journal of Animal Sciences, 2012)
Densified feed blocks of wheat straw (64.2%) along with Stylosanthes hamata meal (13.8%), Leucaena leucocephala leaf meal (13.8%) and Guar gum waste powder (8.2%) were prepared using densifying machine. Average size of the blocks was 30 cm×33 cm×42 cm and average density of blocks was 323.2 kg/m3. Digestibility trial was conducted after one month feeding on two groups (n=6) of Bhadawari male buffaloes (mean weight 230 ± 19 kg). Group 1 was fed with leaf meal added feed blocks (G1) and group 2 with wheat straw and concentrate in the ratio 60:40 in mesh form as a control (G2). DMI was almost comparable (2.51 vs 2.27 kg/100kg bw) however, the DMD (%) was significantly higher G1 (59.2) compared to G2 (51.4). Digestibility coefficients for OM, CP, NFE, NDF, DCP and TDN followed the trend of DM digestibility in Bhadawari buffaloes. Addition of leaf meal with crop residue significantly improved the nutrient digestibility and nutritive value of feed blocks.